Persepsi Siswa SMP tentang Pembelajaran Hybrid IPA dan Pengaruh Kehadiran Live Synchronous terhadap Efektivitas Pendidikan di Jakarta Utara - Avrian Pradiptya (Jurnal Syntax Admiration, 2024)
The impact of Covid-19 on children and families is very felt, namely with the implementation of online or online learning. However, the implementation of full online learning cannot accommodate the needs of all students for education, so other alternative learning methods are needed, namely the hybrid or blended learning method, a learning method that combines face-to-face for some students and online face-to-face for others in each meeting. To find out students' perception of the hybrid learning method and the effectiveness of education with this hybrid method, a researcher is needed on students' perception of hybrid learning and how the relationship between student attendance in live synchronous sessions and educational effectiveness. Data collection was carried out by survey method by distributing questionnaires to 52 respondents of students of a private junior high school in North Jakarta. After that, the data is tested for validity and reliability and then processed using validity and reliability analysis. From the results of the study, it was found that there was a relationship between student perception and educational effectiveness.